Comparison between Self-Assessment and Assessment by the Teacher in Physics at Secondary Leve - Tariq Javed, Muhammad Aslam Asgha (JSE, 2023)
Self-evaluation and evaluation by teacher are considered as the basic ingredients or tools to create awareness about the strengths and weaknesses of the students during the teaching and learning process, through which students are prepared to achieve high academic achievement. The purpose of the study was to compare self-assessment and assessment by the teacher groups in the subject of physics for class IX students.